The Influence of Interpersonal Communication on Student Learning Motivation in Completing Final Projects (Study on Communication Major Class of 2019 at Telkom University's School of Communication and Business) - Wijaksono, Dimas Satrio; Ismail, Oki Achmad; Pramitha, Jalesita Putri (Lingkar Studi Komunikasi (LISKI), 2024)
Aspects of motivation and interpersonal communication are very important in the learning process in college, because motivation will ensure how much effort and encouragement for students in completing education. Not only that, interpersonal communication also affects how students interact with others, to be able to put themselves in a positive atmosphere, so that they can get motivation to be able to complete the final project in achieving a bachelor's degree. The influence of interpersonal communication on students' learning motivation to complete the final project is the subject of this study. This research is based on the theory of self-disclosure proposed by Sydney Marshall Jourad. Quantitative research methods are correlational; Information was collected through questionnaires and analyzed descriptively. The results of this study showed that interpersonal communication skills affected learning motivation to complete the final project by 6.1%. So it can be concluded that interpersonal communication skills have a less significant effect on learning motivation in completing the final project, so it requires other supporting aspects. Keywords: Interpersonal Communication; learning motivation; Final Project Completion